2021
DOI: 10.2196/22220
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based Self-Management Support Prototype for Adults With Chronic Kidney Disease (My Kidneys My Health): Co-Design and Usability Testing

Abstract: Background Supporting patients to self-manage their chronic kidney disease (CKD) has been identified as a research priority by patients with CKD and those who care for them. Self-management has been shown to slow CKD progression and improve the quality of life of individuals living with the disease. Previous work has identified a need for a person-centered, theory-informed, web-based tool for CKD self-management that can be individualized to a patient’s unique situation, priorities, and preferences… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 26 publications
0
39
0
1
Order By: Relevance
“…One of the most widely observed findings in the participatory co-design examples we reviewed in the literature, is that not only should “end-users” (i.e., older adults) be involved more in the research/design process, but that a wide array of “stakeholders” that are non-researchers/non-designers need to be involved as full participants as well (Shaw et al, 2017). As Donald et al (2021) highlights,“[m]eaningful involvement in a co-design process can lead to intuitive and functional AT” (p. 11). Participatory co-design of technology supporting older adults aging in place requires ongoing evaluation with the involvement of older adults (Sumner et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…One of the most widely observed findings in the participatory co-design examples we reviewed in the literature, is that not only should “end-users” (i.e., older adults) be involved more in the research/design process, but that a wide array of “stakeholders” that are non-researchers/non-designers need to be involved as full participants as well (Shaw et al, 2017). As Donald et al (2021) highlights,“[m]eaningful involvement in a co-design process can lead to intuitive and functional AT” (p. 11). Participatory co-design of technology supporting older adults aging in place requires ongoing evaluation with the involvement of older adults (Sumner et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The evidence-informed My Kidneys My Health website ( www.mykidneysmyhealth.com ) was co-developed using a systematic, user-centered design process previously described (Donald et al, 2021a ). The results of our explanatory sequential mixed-methods feasibility study demonstrated that the My Kidneys My Health website had high user acceptance, with a statistically significant increase in perceived self-efficacy sub-scale, gaining information (Donald et al, 2021b ).…”
Section: Design and Methodsmentioning
confidence: 99%
“…My Kidneys My Health was designed based on a conceptual framework identifying optimal design features for eHealth interventions (i.e., interactivity between social context and support, direct contact with the intervention, tailored information, and self-management) (Morrison et al, 2012 ), patient preferences (Donald et al, 2019b ), and behavior change theory (Baay et al, 2019 ). The website supports self-management by “informing” (chronic kidney disease related information); “activating” (prompts/tools to encourage action to manage chronic kidney disease and enhance quality of life); and “collaborating” (links/tools that lead to interaction and engagement with health care professionals and peers) (Donald et al, 2021a ; Gagliardi et al, 2015 ). Specific elements of the website include interactive tools; personalized food list and health care professionals question list; and multimedia education and resources.…”
Section: Design and Methodsmentioning
confidence: 99%
See 2 more Smart Citations